Stranded Cetaceans on the Syrian coast of the Mediterranean Sea - Badran, Mouina (Mesopotamian Journal of Marine Sciences, 2025)
In this study, twenty-two cases of cetacean strandings were recorded along the Syrian coast from 2000 to 2020. The recorded species are: one individual of Megaptera movaeangliae, 4 individuals of Ziphius cavirostris, one individual of Physeter macrocephalus, nine individuals of Tursiops truncatus, two individuals of Balaenoptera physalus, one individual of Grampus griseus, three individuals of Delphinus delphis, And one individual of Balaenoptera acutorostrata. The location and cause of each stranding were registered and are presented and discussed in this paper.